ORGANOLEPTIC QUALITY CHARACTERISTICS OF SAGO NOODLES WITH FORTIFICATION BIANG FISH FLOUR (Ilisha elongata) - Umi Afriana; Sumarto Sumarto; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTIlisha elongata is an economic commodity in the Meranti Islands Regency, Riau Province, the utilization of biang fish is still slight information.However, there is already processing of biang fish into fish flour which needs to be innovative as a regional superior product, such as the fortification of sago noodles. The purpose of this study was to determine the effect of fortification of biangfish flour on the organoleptic quality characteristics. The experimental research method consisted of two stages, 1) fish flour production (I. elongata) and 2) Production ofsago noodles fortified with fish flour (I. elongata) usinga RAL non-factorial with 4 levels, namely P0; (without fish flour), P1 (6% fish flour), P2 (8% fish flour), P3 (10% fish flour), then organoleptic test (quality test on appearance, flavor, texture and odor). The results showed that the fortification of biang fish flour had a significant effect on the organoleptic and chemical quality characteristics of sago noodles. The best treatment was 6% (P1) with the appearance characteristics of the whole sago noodle product, rather interesting food, grayish white, a distinctive scent of sago noodles with a hint of fish; a specific taste typical of the sago noodle and biang fish, and good flavor; bit chewy texture. Thus, fish flour can be used as raw material for manufacture ofsago noodles. Keywords: Fish Flour, Fortification, Sago Noodle